Estimating the Fiscal Costs of Implementing Ghana’s Single Pay Spine Reform - Cavalcanti, Carlos (2012)
Public sector pay policy is one of the main decisions facing a government, as it determines the ability to attract, retain, and motivate staff needed to fulfill its service delivery objectives. One option usually considered is relying on a single pay spine for all services into which jobs would be slotted, thus ensuring greater comparability of similar jobs across the public sector. This paper examines the single spine pay reform currently being considered in Ghana, highlighting the differences between the Ghanaian proposal and similarly named proposals elsewhere, and underscoring the potential cost of implementing the proposal -- which is expected to be significant. There are three main findings: (i) the implementation of the single spine pay reform would raise the base pay wage bill (salaries plus category one allowances) in Ghana to GHC2.8 billion by January 1, 2010 -- an almost 50 percent increase compared with an equivalent figures of GHC1.9 billion at end-2008; (ii) because these estimates focus narrowly on the base pay wage bill, they should be regarded as a lower bound estimate of the overall increase in the wage bill; and (iii) because these estimates are derived from assumptions regarding (1) the distribution of public sector employees across public sector services and institutions; (2) the minimum public sector wage; and the (3) the relativity of all other public sector wages with respect to this minimum wage, they are subject to changes any time these assumptions also change.